دور إدارة السمعة الإلكترونية على إقبال الزبائن على منتجات شركة الجنيدي للألبان - سرحان، عبدالكريم; زبيدي، جمال كامل سعيد (مركز السنبلة للبحوث والدراسات, 2021)
This study seeks to identify the role of online reputation management in promoting demand for the products of Al Juneidi Dairy and Food Products Ltd. The researchers used the descriptive-analytical approach. The population of the study comprised of all the customers of the company in the west bank. A sample of (388) customers of the company were randomly selected, and a questionnaire was used. The study showed a very high response degree regarding the key question of the study. Study results also showed that there are no statistically significant differences at (α = 0.05) regarding the role of online reputation management in promoting customer demand for products of the company that could be attributed to the socio-demographic variables of gender, education level, marital status, age and job type. The researchers recommend setting up a program to use electronic reputation management techniques to change the pre-existing mental image. Increasing interest in electronic reputation management, due to its role in influencing customer demand for the company's products, and implementing field activities and free activities through technological means, increases the opportunity for the company's sales to grow.
تهدف هذه الدراسة إلى التعرف على دور إدارة السمعة الإلكترونية في إقبال الزبائن على منتجات شركة الجنيدي للألبان. واستخدم الباحثان المنهج الوصفي التحليلي، تكون مجتمع الدراسة من جميع المواطنين الذين هم زبائن الشركة في الضفة الغربية، وقام الباحثان باختيار عينة عشوائية مؤلفة من (388) من زبائن تلك الشركة، استخدم الباحثان استبانة كأداة للدراسة. أشارت نتائج الدراسة إلى وجود درجة استجابة مرتفعة جدا على سؤال الدراسة الرئيسي حول دور إدارة السمعة الإلكترونية في إقبال الزبائن على منتجات شركة الجنيدي للألبان، كما أشارت إلى عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α=0.05) في دور إدارة السمعة الإلكترونية في إقبال الزبائن على منتجات شركة الجنيدي للألبان، تعزى لمتغيرات النوع الاجتماعي، المؤهل العلمي، الحالة الاجتماعية، العمر، وطبيعة العمل. يوصي الباحثان بوضع برنامج لإستخدام تقنيات إدارة السمعة الإلكترونية في تغيير الصورة الذهنية المسبقة. وزيادة الاهتمام بإدارة السمعة الإلكترونية، لدورها في التأثير على إقبال الزبائن على منتجات الشركة وتنفيذ نشاطات ميدانية وأنشطة مجانية عبر الوسائل التكنولوجيا تزيد من فرصة نمو المبيعات للشركة.
Keywords: الإدارة الإلكترونية -- إداراة العلاقات العامة -- التسويق -- إدارة علاقات الزبائن